Noninvasive longitudinal quantification of β‐cell mass with [111In]‐labeled exendin‐4. Issue 11 (1st August 2019) - Fujita, Naotaka; Fujimoto, Hiroyuki; Hamamatsu, Keita; Murakami, Takaaki; Kimura, Hiroyuki; Toyoda, Kentaro; Saji, Hideo; Inagaki, Nobuya
Abstract : Currently, quantifying β‐cell mass (BCM) requires harvesting the pancreas. In this study, we investigated a potential noninvasive method to quantify BCM changes longitudinally using [Lys 12 ( 111 In‐BnDTPA‐Ahx)] exendin‐4 ([ 111 In]‐Ex4) and single‐photon emission computed tomography (SPECT). We used autoradiography and transgenic mice expressing green fluorescent protein under the control of mouse insulin 1 gene promotor to evaluate the specificity of [ 111 In]‐Ex4 toward β cells. Using nonobese diabetic (NOD) mice, we injected [ 111 In]‐Ex4 (3.0 MBq) intravenously and performed SPECT 30 min later, repeating this at a 2‐wk interval. After the second scan, we harvested the pancreas and calculated BCM from immunohistochemically stained pancreatic sections. Specific accumulation of [ 111 In]‐Ex4 in β cells was confirmed by autoradiography, with a significant correlation ( r = 0.94) between the fluorescent and radioactive signal intensities. The radioactive signal from the pancreas in the second SPECT scan significantly correlated ( r = 0.89) with BCM calculated from the immunostained pancreatic sections. We developed a regression formula to estimate BCM from the radioactive signals from the pancreas in SPECT scans. BCM can be quantified longitudinally and noninvasively by SPECT imaging with [ 111 In]‐Ex4. This technique successfully demonstrated longitudinal changes in BCM in NOD mice before and after onset of hyperglycemia.—Fujita, N., Fujimoto, H., Hamamatsu, K., Murakami, T., Kimura, H., Toyoda, K., Saji, H., Inagaki, N. Noninvasive longitudinal quantification of β‐cell mass with [ 111 In]‐labeled exendin‐4. FASEB J. 33, 11836‐11844 (2019). www.fasebj.org